VD_FINDINFO HC / 2011 / 520 vom 21. September 2011 - VD Tribunal cantonal (2011)
EXPULSION DE LOCATAIRE, EXÉCUTION FORCÉE | 309 let. a CPC (CH), 319 let. a CPC (CH), 321 al. 2 CPC (CH), 339 al. 2 CPC (CH), 341 CPC (CH)